Positive electrode material for secondary battery and lithium secondary battery comprising same

By using a bimodal mixture of large and small particles in the positive electrode material of lithium secondary battery, adjusting the concentration gradient of transition metal, the problem of insufficient electrode density and thermal stability of lithium secondary battery is solved, and the capacity of the battery is significantly improved and lifespan characteristics.

CN119297216APending Publication Date: 2025-01-10LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311371467.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-11-21
Filing Date
2018-11-21
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing lithium secondary battery positive electrode materials have shortcomings in improving electrode density and thermal stability, and are prone to side reactions with the electrolyte, resulting in reduced capacity and shortened service life.

Method used

Using a bimodal cathode material composed of large particles and small particles, specifically a mixture of large particles with a concentration gradient of the first cathode active material and small particles with a concentration gradient of the second cathode active material, by adjusting the concentration gradient of the transition metal and particle size to improve electrode density and thermal stability and inhibit particle rupture.

Benefits of technology

It significantly improves the electrode density and thermal stability of lithium secondary batteries, extends the battery life, reduces side reactions with the electrolyte, and improves the high capacity and life characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297216A_ABST
    Figure CN119297216A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode material for a secondary battery, a positive electrode for a secondary battery, and a lithium secondary battery, the positive electrode material comprising a first positive electrode active material and a second positive electrode active material, the first positive electrode active material and the second positive electrode active material are composed of a lithium composite transition metal oxide containing at least two transition metals selected from the group consisting of nickel (Ni), cobalt (Co), and manganese (Mn), the average particle diameter (D50) of the first positive electrode active material is at least twice the average particle diameter (D50) of the second positive electrode active material, and in the first positive electrode active material, the average particle diameter (D50) of the first positive electrode active material is at least two times the average particle diameter (D50) of the second positive electrode active material. At least one of Ni, Co and Mn contained in the lithium composite transition metal oxide has a concentration gradient in which the concentration difference between the center and the surface of the particles of the lithium composite transition metal oxide is 1.5 mol% or more.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The application number of the original application is 201880067206.2, the application date is November 21, 2018, and the name of the invention is "Positive electrode material for secondary battery and lithium secondary battery containing the positive electrode material".

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims priority to and the benefit of Korean Patent Application No. 10-2017-0155955, filed on November 21, 2017, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0004] The present invention relates to a positive electrode material for a secondary battery and a lithium secondary battery comprising the positive electrode material. Background Art

[0005] Recently, with the rapid spread of electronic devices (such as mobile phones, laptops and electric vehicles) using batteries, the demand for secondary batteries with small size, light weight and high capacity has risen rapidly. In particular, lithium secondary batteries have attracted attention as driving power sources for portable devices because they are small in size, light in weight and have high energy density. As a result, research and development attempts have been actively carried out to improve the performance of lithium secondary batteries.

[0006] Lithium secondary batteries include an organic electrolyte or a polymer electrolyte filled between a positive electrode and a negative electrode (composed of an active material capable of inserting and extracting lithium ions), and generate electric energy through oxidation and reduction when lithium ions are inserted / extracted into / from the positive and negative electrodes.

[0007] As the positive electrode active material of lithium secondary batteries, compounds such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2 or LiMn2O4) or lithium iron phosphate (LiFePO4) have been used. In addition, as a method of maintaining the excellent reversible capacity of LiNiO2 and improving low thermal stability, lithium composite metal oxides in which part of nickel (Ni) is replaced by cobalt (Co) or manganese (Mn) / aluminum (Al) (hereinafter referred to as "NCM-type lithium composite transition metal oxides" or "NCA-type lithium composite transition metal oxides") have been developed.

[0008] Research has been conducted to increase the capacity per unit volume of lithium composite transition metal oxides and enhance stability by forming a metal component concentration gradient, increasing the nickel content, or increasing the rolling density of the positive electrode active material layer. However, there is still a need to develop a positive electrode active material having a high capacity and satisfying excellent thermal stability. Summary of the invention

[0009] [Technical issues]

[0010] The present invention aims to provide a positive electrode material for a secondary battery, which increases the electrode density of the positive electrode, has a high capacity, improves thermal stability, and prevents particles of a positive electrode active material from being broken to thereby suppress a side reaction with an electrolyte.

[0011] [Technical solution]

[0012] The present invention provides a positive electrode material for a secondary battery, which comprises a first positive electrode active material and a second positive electrode active material, wherein the first positive electrode active material and the second positive electrode active material are composed of a lithium composite transition metal oxide containing at least two transition metals selected from the group consisting of nickel (Ni), cobalt (Co) and manganese (Mn), and the average particle size (D 50 ) is the average particle size of the second positive electrode active material (D 50 ), the first positive electrode active material has the following concentration gradient: the concentration difference between the center and the surface of the particles of the lithium composite transition metal oxide of at least one of Ni, Co and Mn contained in the lithium composite transition metal oxide is 1.5 mol% or more.

[0013] In addition, the present invention provides a positive electrode and a lithium secondary battery comprising the positive electrode material.

[0014] [Beneficial Effects]

[0015] According to the present invention, by using a mixture of large particles with a concentration gradient as a first positive electrode active material and small particles without a concentration gradient as a second positive electrode active material, the electrode density of the positive electrode can be increased, and high capacity and excellent thermal stability can be ensured. In addition, the small particles without a concentration gradient can prevent the particles of the large particles with a concentration gradient from breaking, thereby suppressing side reactions with the electrolyte.

[0016] A lithium secondary battery manufactured using the secondary battery cathode material of the present invention can have high capacity and enhanced battery characteristics such as lifespan characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a graph showing the leakage currents of lithium secondary battery cells using the positive electrodes produced in Examples and Comparative Examples.

[0018] Figure 2 This is a diagram for evaluating the life characteristics of lithium secondary battery cells using the positive electrodes produced in Examples and Comparative Examples. DETAILED DESCRIPTION

[0019] Hereinafter, the present invention will be described in more detail to help understand the present invention. The terms or words used in the specification and claims should not be interpreted as limited to the general or dictionary meaning, but should be interpreted based on the concept of the inventor to appropriately define the terms to best explain the principle of the present invention, using the meaning and concept consistent with the technical concept of the present invention.

[0020] The positive electrode material for a secondary battery of the present invention comprises a first positive electrode active material and a second positive electrode active material, wherein the first positive electrode active material and the second positive electrode active material are composed of a lithium composite transition metal oxide containing at least two transition metals selected from the group consisting of nickel (Ni), cobalt (Co) and manganese (Mn), and the average particle size (D 50 ) is the average particle size of the second positive electrode active material (D 50 ), the first positive electrode active material has the following concentration gradient: the concentration difference between the center and the surface of the particles of the lithium composite transition metal oxide of at least one of Ni, Co and Mn contained in the lithium composite transition metal oxide is 1.5 mol% or more.

[0021] The cathode material for a secondary battery of the present invention contains large particles as a first cathode active material and small particles as a second cathode active material.

[0022] In order to increase the capacity per unit volume of the positive electrode for secondary batteries, it is necessary to increase the density of the positive electrode active material layer. As a method for increasing the density of the positive electrode active material layer, a method for increasing the rolling density (or electrode density) by reducing the gaps between the positive electrode active material particles has been used. In the case of a bimodal positive electrode material in which large particles and small particles of a positive electrode active material are mixed as described in the present invention, the free space between the large particles of the positive electrode active material can be filled with small particles of the positive electrode active material, and therefore, the positive electrode density can be increased by packing more densely.

[0023] The average particle size of the first positive electrode active material (D 50 ) is the average particle size of the second positive electrode active material (D 50 ) more than twice.

[0024] In the present invention, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% volume accumulation in the particle size distribution curve. The average particle size (D 50 ) can be measured using, for example, a laser diffraction method. For example, according to a method for measuring the average particle size (D 50), the particles of the positive electrode active material are dispersed in a dispersion medium and the dispersion is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), and ultrasonic waves of about 28 kHz are applied at an output of 60 W, after which the average particle size (D ) corresponding to 50% volume accumulation in the measuring device can be calculated. 50 ).

[0025] More preferably, the average particle size (D 50 ) can be 5:1 to 2:1, and most preferably 4:1 to 2.5:1. 50 ) when the ratio satisfies the above range, the voids between the particles of the positive electrode active material can be more effectively reduced, the packing density can be increased, the density of the positive electrode can be increased, and the capacity per unit volume of the positive electrode can be effectively increased.

[0026] Specifically, the average particle size (D 50 ) can be 10 to 30 μm, more preferably 13 to 25 μm, and most preferably 15 to 22 μm.

[0027] The average particle size of the second positive electrode active material (D 50 ) can be 1 to 10 μm, more preferably 2 to 8 μm, and most preferably 3 to 6 μm.

[0028] The first positive electrode active material and the second positive electrode active material of the present invention are composed of a lithium composite transition metal oxide containing at least two transition metals selected from the group consisting of Ni, Co and Mn. Here, the first positive electrode active material as a large particle is a lithium composite transition metal oxide with a concentration gradient, and the second positive electrode active material as a small particle is a lithium composite transition metal oxide without a concentration gradient. Similarly, by using a mixture of large particles with a concentration gradient and small particles without a concentration gradient, higher capacity and thermal stability can be ensured, and small particles without a concentration gradient can prevent the particles of large particles with a concentration gradient from breaking, thereby inhibiting side reactions with the electrolyte.

[0029] The first positive electrode active material is a lithium composite transition metal oxide having a metal component concentration gradient, wherein the concentration difference between the center and the surface of the lithium composite transition metal oxide of at least one of Ni, Co and Mn contained in the lithium composite transition metal oxide is 1.5 mol% or more. The concentration difference between the center and the surface of the particles of the lithium composite transition metal oxide of Ni contained in the lithium composite transition metal oxide is preferably 2 mol% or more, more preferably 3 mol% or more.

[0030] In the present invention, the concentration gradient and concentration of the transition metal in the positive electrode active material can be identified using methods such as electron probe microanalysis (EPMA), inductively coupled plasma atomic emission spectroscopy (ICP-AES), time-of-flight secondary ion mass spectrometry (ToF-SIMS), EDAX-SEM analysis, or X-ray photoelectron spectroscopy (XPS). Specifically, the atomic ratio of the metal can be measured using EPMA while moving from the center of the positive electrode active material to its surface, or the atomic ratio of the metal can be measured by etching from the surface of the positive electrode active material to its center and using XPS.

[0031] In an exemplary embodiment of the present invention, the first positive electrode active material may have a concentration gradient in which the concentration of at least one of Ni, Co, and Mn contained in the lithium composite transition metal oxide gradually changes from the center to the surface of the lithium composite transition metal oxide particle.

[0032] More preferably, the first positive electrode active material may have a concentration gradient in which the Ni concentration gradually decreases from the center to the surface of the lithium composite transition metal oxide particle. Since the Ni concentration is kept high at the center of the first positive electrode active material particle and decreases toward the surface of the particle, thermal stability can be exhibited and capacity reduction can be prevented.

[0033] Alternatively, at least one of Mn and Co may have a concentration gradient in which its concentration in the lithium composite transition metal oxide particles gradually increases from the center of the particles to the surface. In this case, since the Mn concentration is kept low at the center of the particles of the first positive electrode active material and increases toward the particle surface, excellent thermal stability can be obtained without capacity reduction. Since the Co concentration can be kept low at the center of the particles of the first positive electrode active material and increase toward the particle surface, the amount of Co can be reduced and the capacity reduction can be prevented.

[0034] The first positive electrode active material of the exemplary embodiment of the present invention may have a continuous concentration gradient in which the Ni concentration in the first positive electrode active material decreases from the center of the particle thereof to the surface layer, and may have a continuous concentration gradient complementary to the concentration gradient of Ni in which the concentration of at least one of Mn and Co increases from the center of the particle to the surface. Likewise, due to such a concentration gradient of the components (from the center to the surface of the particle of the first positive electrode active material, the Ni concentration gradually decreases, and the Mn and / or Co concentration gradually increases), the capacity characteristics may be maintained, and thermal stability may be exhibited.

[0035] In the present invention, "a concentration gradient showing a gradual change (increase or decrease) in the concentration of the transition metal" means that there is a concentration distribution in which the concentration of the transition metal gradually changes throughout the particle. Specifically, the concentration distribution shows that the difference in the concentration of the transition metal per 1 μm in the particle can be 0.1 to 5 mol%, more specifically 0.1 to 3 mol%, and even more specifically 1 to 2 mol%, based on the total number of moles of the corresponding metal contained in the positive electrode active material.

[0036] Since the first positive electrode active material having large particles has a concentration gradient in which the concentration of the transition metal element varies according to the position in the particle, the characteristics of the corresponding transition metal can be easily used to further enhance the battery performance improvement effect of the positive electrode active material. In addition, according to an exemplary embodiment of the present invention, when the transition metal in the first positive electrode active material particle has a concentration gradient in which the concentration of the transition metal in the particle changes continuously, there is no drastic phase boundary region from the starting point of the shell to its end point, so the crystal structure can be stabilized and the thermal stability can be improved. In addition, when the slope of the concentration gradient of the transition metal is constant, the effect of improving the structural stability can be further enhanced.

[0037] Meanwhile, the second positive electrode active material is a lithium composite transition metal oxide having no concentration gradient of a metal component (including at least one of Ni, Co, and Mn).

[0038] According to an exemplary embodiment of the present invention, the first positive electrode active material and the second positive electrode active material may be a lithium composite transition metal oxide containing Ni, Co and at least one selected from the group consisting of Mn and Al. For example, the first positive electrode active material and the second positive electrode active material may be an NCM-type lithium composite transition metal oxide containing Ni, Co and Mn, an NCA-type lithium composite transition metal oxide containing Ni, Co and Al, or a four-component lithium composite transition metal oxide mainly containing four components such as Ni, Co, Mn and Al.

[0039] In addition, the first positive electrode active material and the second positive electrode active material of the exemplary embodiment of the present invention may be high Ni positive electrode active materials, wherein the Ni content may be 60 mol % or more in all metal elements contained in the lithium composite transition metal oxide. In all metal elements, the Ni content is preferably 70 mol % or more, more preferably 80 mol % or more. When using high Ni first and second positive electrode active materials having a Ni content of 60 mol % or more in all metal elements, a higher capacity can be ensured.

[0040] Meanwhile, the first and second positive electrode active materials may be lithium composite transition metal oxides having the same or different compositions.

[0041] More specifically, the first and second positive electrode active materials may be lithium composite transition metal oxides represented by Chemical Formula 1 below.

[0042] [Chemical Formula 1]

[0043] Li p Ni 1-(x1+y1+z1) Co x1 M a y1 M b z1 M c q1 O2

[0044] In this chemical formula, M a is at least one element selected from the group consisting of Mn and Al, M b is at least one element selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb, and Mo, M c is at least one element selected from the group consisting of Al, Zr, Ti, Mg, Ta, Nb, Mo, and Cr, 0.9 ≤ p ≤ 1.5, 0 < x1 ≤ 0.4, 0 < y1 ≤ 0.4, 0 ≤ z1 ≤ 0.1, 0 ≤ q1 ≤ 0.1, 0 < x1 + y1 + z1 ≤ 0.4.

[0045] In the lithium composite transition metal oxide of Chemical Formula 1, the content of Li may be p, that is, 0.9 ≤ p ≤ 1.5. When p is less than 0.9, there is a possibility of capacity reduction. When p is greater than 1.5, it may be difficult to prepare the positive electrode active material because the particles sinter during the calcination process. Considering the significant improvement in the capacity characteristics of the positive electrode active material obtained by controlling the Li content and the balance of the calcination property in the preparation of the active material, the Li content is more preferably 1.0 ≤ p ≤ 1.15.

[0046] In the lithium composite transition metal oxide of Chemical Formula 1, the content of Ni may correspond to 1 - (x1 + y1 + z1). For example, 0.6 ≤ 1 - (x1 + y1 + z1) < 1. When the Ni content in the lithium composite transition metal oxide of Chemical Formula 1 is 0.6 or more, a sufficient amount of Ni contributing to charge and discharge can be ensured to achieve high capacity. More preferably, the Ni content may be 0.8 ≤ 1 - (x1 + y1 + z1) ≤ 0.99.

[0047] In the lithium composite transition metal oxide of Chemical Formula 1, the Co content may be x1, that is, 0 < x1 ≤ 0.4. When the Co content in the lithium composite transition metal oxide of Chemical Formula 1 is greater than 0.4, additional costs may be incurred. Considering the significant improvement in capacity characteristics due to the inclusion of Co, the Co content is more specifically 0.05 ≤ x1 ≤ 0.2.

[0048] In the lithium composite transition metal oxide of Chemical Formula 1, M a can be Mn or Al, or both Mn and Al. These metal elements can enhance the stability of the active material, resulting in an improvement in battery stability. Considering the effect of improving the life characteristics, the content of M a can be y1, that is, 0 < y1 ≤ 0.4. When y1 of the lithium composite transition metal oxide of Chemical Formula 1 is greater than 0.4, the output characteristics and capacity characteristics of the battery may deteriorate instead. The content of M a is more specifically 0.05 ≤ y1 ≤ 0.2.

[0049] In the lithium composite transition metal oxide of Chemical Formula 1, M b can be a doping element contained in the crystal structure of the lithium composite transition metal oxide. The content of M b can be z1, that is, 0 ≤ z1 ≤ 0.1.

[0050] In the lithium composite transition metal oxide of Chemical Formula 1, the metal element M c may not be included in the structure of the lithium composite transition metal oxide, and the lithium composite transition metal oxide doped with M c can be prepared as follows: adding a precursor and a lithium source during the mixing and calcination process of the precursor and the lithium source and calcining the M c source together with the precursor and the lithium source, or forming a lithium composite transition metal oxide and then calcining it together with the separately added M c source. Without deteriorating the characteristics of the positive electrode active material, the content of M c can be q1, that is, 0 ≤ q1 ≤ 0.1.

[0051] Meanwhile, since the second positive electrode active material in the form of small particles may have poor thermal stability, a coating containing a lithium oxide can be provided on at least a part of the surface of the particles of the second positive electrode active material. The lithium oxide contains at least one selected from the group consisting of boron (B) and manganese (Mn). For example, the coating of the second positive electrode active material can contain a lithium borate (such as LiBO2, Li2B4O7 or LiB3O5), a lithium manganate (such as LiMn2O4) or a mixture thereof.

[0052] In an exemplary embodiment of the present invention, the first and second positive electrode active materials may be mixed in a mixing ratio of 9:1 to 1:9, more preferably 8:2 to 3:7, and most preferably 8:2 to 5:5. By using a mixture of a first positive electrode active material as a large particle and having a concentration gradient and a second positive electrode active material as a small particle and having no concentration gradient, the electrode density of the positive electrode can be increased, high capacity and excellent thermal stability can be ensured, and side reactions with the electrolyte can be suppressed. Therefore, a lithium secondary battery manufactured using the above-mentioned positive electrode active material can have a high capacity and can enhance battery characteristics, such as life characteristics.

[0053] According to another exemplary embodiment of the present invention, a positive electrode for a lithium secondary battery and a lithium secondary battery including the positive electrode material are provided.

[0054] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode mixture layer formed on the positive electrode current collector and including the positive electrode material.

[0055] In the positive electrode, the positive electrode collector is not particularly limited as long as it does not cause chemical changes in the battery and has conductivity, and can be stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium or silver. In addition, the thickness of the positive electrode collector can generally be 3 to 500 μm, and the bonding strength of the positive electrode active material can be increased by forming fine irregularities on the surface of the positive electrode collector. For example, the positive electrode collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.

[0056] Furthermore, the positive electrode mixture layer may contain a conductive material and a binder in addition to the above-mentioned positive electrode material.

[0057] Here, the conductive material is used to provide conductivity to the electrode, without particular limitation, as long as it has electronic conductivity and does not cause chemical changes in the battery. Specific examples of conductive materials may include: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber composed of copper, nickel, aluminum or silver; conductive whiskers, such as zinc oxide whiskers or potassium titanate whiskers; conductive metal oxides, such as titanium dioxide; or conductive polymers, such as polyphenylene derivatives, and one or a mixture of two or more thereof can be used. The content of the conductive material can generally be 1% to 30% by weight based on the total weight of the positive electrode active material layer.

[0058] In addition, the binder is used to enhance the bonding between the positive active material particles and the bonding between the positive active material and the positive current collector. Specific examples of the binder can be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and one or a mixture of two or more thereof can be used. Based on the total weight of the positive active material layer, the content of the binder can be 1% to 30% by weight.

[0059] In addition to using the above-mentioned positive electrode materials, the positive electrode can be prepared according to a conventional positive electrode preparation method. Specifically, the positive electrode can be manufactured by coating a positive electrode mixture layer-forming composition (which includes the above-mentioned positive electrode active material and optional conductive agent and binder) on a positive electrode current collector, and then drying and rolling the composition. Here, the types and contents of the positive electrode active material, binder and conductive material are as described above.

[0060] The solvent may be a commonly used solvent in the art, and may be dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water, and one or a mixture of two or more thereof may be used. Considering the coating thickness and manufacturing yield of the slurry, the amount of the solvent is sufficient to dissolve or disperse the positive electrode active material, the conductive material and the binder, and then provide a viscosity showing excellent thickness uniformity when the slurry is coated to prepare the positive electrode.

[0061] As another method, the positive electrode can be produced by casting the positive electrode mixture layer-forming composition on a separate support, and laminating the film obtained by peeling off the support on a positive electrode current collector.

[0062] According to another exemplary embodiment of the present invention, an electrochemical device including the positive electrode is provided. The electrochemical device may be specifically a battery or a capacitor, more specifically, a lithium secondary battery.

[0063] The lithium secondary battery specifically includes a positive electrode, a negative electrode arranged opposite to the positive electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is as described above. In addition, the lithium secondary battery may selectively include a battery housing for accommodating an electrode assembly including a positive electrode, a negative electrode and a separator, and a sealing component for sealing the battery housing.

[0064] In a lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode mixture layer located on the negative electrode current collector.

[0065] The negative electrode current collector is not specifically limited as long as it has high conductivity and does not cause chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, or copper or stainless steel surface-treated with carbon, nickel, titanium or silver, or aluminum-cadmium alloy. In addition, the thickness of the negative electrode current collector may generally be 3 μm to 500 μm, and, like the positive electrode current collector, fine irregularities may be formed on the surface of the current collector to enhance the adhesion strength of the negative electrode active material. For example, the negative electrode current collector may be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0066] In addition to the negative electrode active material, the negative electrode mixture layer may optionally include a binder and a conductive material. For example, the negative electrode mixture layer may be prepared by coating a negative electrode forming composition (which includes a negative electrode active material and optional binder and conductive material) on a negative electrode current collector and drying the composition, or casting the negative electrode forming composition on a separate carrier and laminating the film obtained by peeling off the carrier on the negative electrode current collector.

[0067] As the negative electrode active material, a compound capable of reversibly inserting and deinserting lithium can be used. Specific examples of the negative electrode active material may be: carbon-based materials such as artificial graphite, natural graphite, graphitized carbon fiber, or amorphous carbon; metal compounds that can be alloyed with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; metal oxides that can be doped and dedoped with lithium, such as SiO β (0<β<2), SnO2, vanadium oxide and lithium vanadium oxide; or a composite comprising a metal compound and a carbon-based material, such as a Si-C composite or a Sn-C composite, and any one of them or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include irregular, planar, flaky, spherical or fibrous natural graphite or artificial graphite, floating (kish) graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microbeads, mesophase pitch and high-temperature sintered carbon (e.g., coke derived from petroleum or coal tar pitch).

[0068] In addition, the binder and the conductive agent may be the same as described above for the positive electrode.

[0069] Meanwhile, in lithium secondary batteries, the separator is not specifically limited, as long as it is commonly used in lithium secondary batteries to separate the negative electrode and the positive electrode and provide a mobile path for lithium ions, specifically, the separator has low resistance to the movement of electrolyte ions and is excellent in the ability to penetrate electrolyte. Specifically, a porous polymer film can be used, such as a porous polymer film prepared by a polyolefin polymer (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer), or a laminated structure comprising more than two layers thereof. In addition, conventional porous nonwoven fabrics can be used, such as nonwoven fabrics formed by high melting point glass fibers or polyethylene terephthalate fibers. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a monolayer or multilayer structure.

[0070] In addition, the electrolyte used in the present invention may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel polymer electrolyte, a solid inorganic electrolyte or a molten inorganic electrolyte that can be used to manufacture a lithium secondary battery, but the present invention is not limited thereto.

[0071] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0072] There is no particular limitation on the organic solvent, as long as it can act as a medium that enables the ions involved in the electrochemical reaction of the battery to move through. Specifically, the organic solvent can be: an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene and fluorobenzene; a carbonate solvent such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); an alcohol solvent such as ethanol or isopropanol; a nitrile solvent such as R-CN (wherein R is a linear, branched or cyclic C2 to C20 hydrocarbon group, and may include a double bond aromatic ring or an ether bond); an amide solvent such as dimethylformamide; a dioxolane solvent such as 1,3-dioxolane; or a sulfolane solvent. In these solvents, carbonate solvents are preferably used, and more preferably a mixture of a cyclic carbonate (such as ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant and a low-viscosity straight-chain carbonate compound (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) that improves the charge / discharge performance of the battery. In this case, when a mixture of a volume ratio of about 1:1 to about 1:9 of a cyclic carbonate and a chain carbonate is used, the electrolyte can show excellent performance.

[0073] The lithium salt is not particularly limited as long as it is a compound that can provide lithium ions used in lithium secondary batteries. Specifically, the lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2. The concentration of the lithium salt is preferably 0.1M to 2.0M. When the concentration of the lithium salt is included in the above range, the electrolyte has suitable conductivity and viscosity, so it can show excellent electrolytic performance. Therefore, lithium ions can be effectively migrated.

[0074] In order to enhance the life characteristics of the battery, inhibit the decline of the battery capacity and increase the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, the electrolyte may further include one or more additives, for example, halogenated alkylene carbonate compounds (such as difluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N, N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol or aluminum chloride. At this time, based on the total weight of the electrolyte, the content of the additive may be 0.1 wt % to 5 wt %.

[0075] Since the lithium secondary battery including the positive electrode active material of the present invention stably shows excellent discharge capacity, excellent output characteristics and excellent capacity retention rate, it can be used in portable devices (such as mobile phones, notebook computers and digital cameras) and electric vehicle fields (such as hybrid electric vehicles (HEV)).

[0076] Therefore, according to still another exemplary embodiment of the present invention, a battery module including the lithium secondary battery as a unit cell and a battery pack including the battery module are provided.

[0077] The battery module or battery pack can be used as a power source for any one or more medium to large devices, including: power tools; electric motor vehicles, such as electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs); and energy storage systems.

[0078] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the embodiments described herein.

[0079] Example 1

[0080] As the first positive electrode active material, lithium composite transition metal oxide LiNi 0.88 Co 0.10 Mn 0.02 O2 particles (D 50 =16μm), the Ni content at the center of the particle is 89 mol%, the Ni content at the surface of the particle is 86 mol%, and has the following concentration gradient: from the center of the particle to the surface, the Ni concentration gradually decreases, while the Co and Mn concentrations gradually increase.

[0081] As the second positive electrode active material, lithium composite transition metal oxide LiNi 0.88 Co 0.10 Mn 0.02 O2 particles (D 50 =5 μm), which has no concentration gradient.

[0082] The first positive electrode active material and the second positive electrode active material are mixed in a weight ratio of 8:2 before use, and the positive electrode material, carbon black conductive material and PVdF binder are mixed in an N-methylpyrrolidone solvent in a weight ratio of 96.5:1.5:2.0 to form a positive electrode forming composition, and the composition is coated on one surface of an aluminum current collector, dried at 130°C and roll-pressed to prepare a positive electrode.

[0083] Example 2

[0084] The positive electrode was prepared in the same manner as in Example 1, except that a lithium composite transition metal oxide LiNi was used as the first positive electrode active material. 0.92 Co 0.04 Mn 0.04 O2 particles (D 50 =14μm), the Ni content at the center of the particle is 93 mol%, the Ni content at the surface of the particle is 90 mol%, and has the following concentration gradient: from the center of the particle to the surface, the Ni concentration gradually decreases, and the Co and Mn concentrations gradually increase; as the second positive electrode active material, a lithium composite transition metal oxide LiNi is used 0.92 Co 0.04 Mn 0.04 O2 particles (D 50 =4 μm), which has no concentration gradient and forms a coating comprising lithium boron oxide on the particle surface.

[0085] Example 3

[0086] The positive electrode was prepared in the same manner as in Example 1, except that a lithium composite transition metal oxide LiNi was used as the first positive electrode active material.0.87 Co 0.08 Mn 0.03 Al 0.02 O2 particles (D 50 =16μm), the Ni content at the particle center is 88 mol%, the Ni content at the particle surface is 86 mol%, and has the following concentration gradient: from the particle center to the surface, the Ni concentration gradually decreases, and the Co and Mn concentrations gradually increase; as the second positive electrode active material, a lithium composite transition metal oxide LiNi is used 0.88 Co 0.09 Mn 0.03 O2 particles (D 50 =5 μm), which has no concentration gradient and forms a coating comprising lithium boron oxide on the particle surface.

[0087] Example 4

[0088] The positive electrode was prepared in the same manner as in Example 1, except that a lithium composite transition metal oxide LiNi was used as the first positive electrode active material. 0.70 Co 0.10 Mn 0.20 O2 particles (D 50 =16μm), the Ni content at the particle center is 72 mol%, the Ni content at the particle surface is 69 mol%, and has the following concentration gradient: from the particle center to the surface, the Ni concentration gradually decreases, and the Co and Mn concentrations gradually increase; as the second positive electrode active material, a lithium composite transition metal oxide LiNi is used 0.70 Co 0.10 Mn 0.20 O2 particles (D 50 =5 μm), which has no concentration gradient and forms a coating comprising lithium boron oxide on the particle surface.

[0089] Comparative Example 1

[0090] The positive electrode was prepared in the same manner as in Example 1, except that a lithium composite transition metal oxide LiNi was used as the positive electrode active material. 0.88 Co 0.10 Mn 0.02 O2 single peak particle (D 50 =12μm), the Ni content at the center of the particle is 89 mol%, the Ni content at the surface of the particle is 87 mol%, and has the following concentration gradient: from the center of the particle to the surface, the Ni concentration gradually decreases, and the Co and Mn concentrations gradually increase.

[0091] Comparative Example 2

[0092] The positive electrode was prepared in the same manner as described in Example 1, except that a lithium composite transition metal oxide LiNi without a concentration gradient was used as the first positive electrode active material. 0.83 Co 0.11 Mn 0.06 O2 particles (D 50 =16 μm), and as the second positive electrode active material, a lithium composite transition metal oxide LiNi with no concentration gradient was used. 0.83 Co 0.11 Mn 0.06 O2 particles (D 50 =5μm).

[0093] [Experimental Example 1: Evaluation of Rolling Density and Large Particle Breakage]

[0094] The rolling density and the degree of breakage of large particles of the positive electrodes prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were evaluated. The results are shown in Table 1.

[0095] The roll density was measured by densely filling a cylindrical container with a 5 g aliquot of each of the positive electrode active materials used in Examples 1 to 4 and Comparative Examples 1 and 2, and then measuring the density of the powder at 2,000 kgf while applying a pressure of 400 kgf to 2,000 kgf at a lifting pressure of 400 kgf.

[0096] The degree of breakage of the large particles was observed using an energy dispersive X-ray spectrometer (EDS) connected to a scanning electron microscope (SEM), and more specifically, a cross section of a rolled electrode was prepared as a sample to observe the particle distribution through EDS mapping at the same magnification. The number of broken large particles among all the large particles in the mapping was counted, thereby estimating the degree of breakage of the large particles.

[0097] [Table 1]

[0098] <![CDATA[Rolled density (g / cm 3 )]]> Breakage of large particles (%) Example 1 3.33 18 Example 2 3.35 15 Example 3 3.31 20 Example 4 3.01 16 Comparative Example 1 3.13 60 Comparative Example 2 3.31 41

[0099] Referring to Table 1, compared with Comparative Example 1 using a unimodal positive electrode material, Examples 1 to 3 using a mixture of a first positive electrode active material as large particles and having a concentration gradient and a second positive electrode active material as small particles and having no concentration gradient are enhanced in rolling density. In addition, compared with Comparative Example 2 using large particles and small particles without a concentration gradient, the degree of breakage of the large particles in Examples 1 to 4 using bimodal large particles and small particles is significantly reduced.

[0100] [Experimental Example 2: Evaluation of Side Reaction and Leakage Current of Electrolyte]

[0101] The positive electrodes prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were used to manufacture lithium secondary battery half cells.

[0102] Specifically, 300 μm lithium metal was used as the negative electrode.

[0103] The electrode assembly is prepared by placing a porous polyethylene separator between the positive and negative electrodes prepared in advance as above, placing it in a shell, and then injecting 80 μl of electrolyte into the shell to manufacture a lithium secondary battery. Here, the electrolyte is prepared as follows: 1.0M lithium hexafluorophosphate (LiPF6) and vinylene carbonate / propane sultone / ethylene sulfate (mixing volume ratio of VC / PS / Esa=3 / 0.5 / 1) as additives are dissolved in an organic solvent composed of ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate (mixing volume ratio of EC / DMC / EMC=3 / 4 / 3).

[0104] After wetting for 10 hours, the lithium secondary battery half-cells made using each of the positive electrodes prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were formed in the following manner: the half-cell was charged to 4.25V at a 0.2C current proportional to the mass of the positive electrode active material, and discharged to 2.5V at the same current (i.e., 0.2C). Subsequently, the leakage current was measured by the following method: after charging to 4.7V at a constant current of 0.1C and then maintaining the voltage at 4.7V for 120 hours, the current level was measured without maintaining a constant current, and the results are shown in Tables 2 and 3 below. Figure 1 In order to compare the positive electrode active materials under the same conditions, an average leakage current level obtained by integrating the leakage current level generated for 120 hours and dividing the integrated value by 120 hours was used.

[0105] [Table 2]

[0106]

[0107] See Table 2 and Figure 1 , it can be seen that the 120-hour average leakage current in Examples 1 to 4 using a mixture of a first positive electrode active material as a large particle and having a concentration gradient and a second positive electrode active material as a small particle and having no concentration gradient is significantly reduced compared to Comparative Example 1 using a single-peak positive electrode active material. In addition, compared to Comparative Example 2 using large particles and small particles without a concentration gradient, it can be confirmed that in Examples 1 to 4, despite the bimodality of large particles and small particles, the average leakage current is still significantly reduced, and the difference in leakage current becomes more prominent from about 100 hours. It is believed that this is because Examples 1 to 4 using a mixture of a first positive electrode active material as a large particle and having a concentration gradient and a second positive electrode active material as a small particle and having no concentration gradient reduce the breakage of large particles, thereby suppressing side reactions with the electrolyte.

[0108] [Experimental Example 3: Evaluation of Lifespan Characteristics]

[0109] As described in Experimental Example 2, for lithium secondary battery half cells manufactured using each of the positive electrodes prepared in Examples 1 to 4 and Comparative Examples 1 and 2, the capacity retention rate at 45°C and 0.33C current for 30 cycles of charge / discharge was measured, thereby evaluating the high temperature life characteristics. The results are shown in Tables 3 and Figure 2 middle.

[0110] [Table 3]

[0111]

[0112] See Table 3 and Figure 2 In Examples 1 to 4 using a mixture of a first positive electrode active material as large particles having a concentration gradient and a second positive electrode active material as small particles having no concentration gradient, side reactions with the electrolyte are suppressed by reducing the breakage of large particles, thereby producing excellent high temperature life characteristics, compared to Comparative Example 1 using unimodal particles having a concentration gradient or Comparative Example 2 using bimodal large particles and small particles having no concentration gradient.

Claims

1. A positive electrode material for a secondary battery, comprising: a first positive electrode active material and a second positive electrode active material, in, The first positive electrode active material and the second positive electrode active material are lithium composite transition metal oxides containing two or more transition metals selected from the group consisting of nickel (Ni), cobalt (Co) and manganese (Mn), The average particle size of the first positive electrode active material (D 50 ) is the average particle size of the second positive electrode active material (D 50 ), and The first positive electrode active material has the following concentration gradient: the concentration difference between the center and the surface of the particles of the lithium composite transition metal oxide of at least one of Ni, Co and Mn contained in the lithium composite transition metal oxide is 1.5 mol % or more; The second positive electrode active material has no metal component concentration gradient; The second positive electrode active material further comprises a coating layer on at least a portion of the particle surface, and the coating layer comprises a lithium oxide containing boron (B); The first positive electrode active material and the second positive electrode active material are represented by the following chemical formula 1: [Chemical formula 1] Li p Ni 1-(x1+y1+z1) Co x1 M a y1 M b z1 M c q1 O2 Among them, M a is at least one element selected from the group consisting of Mn and Al, M b is at least one element selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb and Mo, M c is at least one element selected from the group consisting of Al, Zr, Ti, Mg, Ta, Nb, Mo and Cr, and 0.9≤p≤1.5, 0 <x1≤0.4,0<y1≤0.4,0≤z1≤0.1,0≤q1≤0.1,0<x1+y1+z1≤0.4,0.8≤1-(x1+y1+z1)≤0.99。 2. The positive electrode material according to claim 1, wherein The first positive electrode active material has a concentration gradient in which the concentration of at least one of Ni, Co, and Mn contained in the lithium composite transition metal oxide gradually changes from the center to the surface of a particle of the lithium composite transition metal oxide.

3. The positive electrode material according to claim 1, wherein The first positive electrode active material has a concentration gradient in which the concentration of Ni gradually decreases from the center to the surface of particles of the lithium composite transition metal oxide.

4. The positive electrode material according to claim 1, wherein The first positive electrode active material has a concentration gradient in which the concentration of at least one of Mn and Co gradually increases from the center to the surface of particles of the lithium composite transition metal oxide.

5. The positive electrode material according to claim 1, wherein The first positive electrode active material and the second positive electrode active material include a lithium composite transition metal oxide containing Ni, Co, Mn, and Al.

6. The positive electrode material according to claim 1, wherein The first positive electrode active material and the second positive electrode active material are lithium composite transition metal oxides having the same or different compositions.

7. The positive electrode material according to claim 1, wherein The average particle size (D 50 ) is 5:1~2:

1.

8. The positive electrode material according to claim 1, wherein The average particle size of the first positive electrode active material (D 50 ) is 10~30μm.

9. The positive electrode material according to claim 1, wherein The average particle size of the second positive electrode active material (D 50 ) is 1 to 10 μm.

10. The positive electrode material according to claim 1, wherein The first positive electrode active material and the second positive electrode active material are mixed in a weight ratio of 9:1 to 1:

9. 11 . A positive electrode for a secondary battery, comprising the positive electrode material according to claim 1 . 12 . A lithium secondary battery comprising the positive electrode according to claim 11 .